PRAGMATIC FUNCTION OF RELIGIOUSLY MARKED ALLUSIONS IN THE LITERARY TEXT (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
Religiously marked allusions create a constant associative attachment to the precedent religious text, by activating religious knowledge structures kept in people's conceptual worldview referring to both the source and recipient texts. Religiously marked allusions are assigned as means of indirect conveyance of the author’s modality in the literary text and its correct interpretation remarkably contributes to the successful revelation of the author’s individual world picture.